2021
DOI: 10.1007/s40881-021-00114-8
|View full text |Cite
|
Sign up to set email alerts
|

Lab-like findings from online experiments

Abstract: Laboratory experiments have been often replaced by online experiments in the last decade. This trend has been reinforced when academic and research work based on physical interaction had to be suspended due to restrictions imposed to limit the spread of Covid-19. Therefore, data quality and results from web experiments have become an issue which is currently investigated. Are there significant differences between lab experiments and online findings? We contribute to this debate via an experiment aimed at compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…The data collected in both online and laboratory settings produced similar results. These findings are in line with studies showing no significant differences in results of online and in lab experiments (Buso, I.M., Di Cagno, D., Ferrari, L. et al 2021). Earlier studies have established that the perceptual nature of the experiment does not get significantly influenced by the experimental setting (Germine, L., Nakayama, K., Duchaine, B.C.…”
Section: Resultssupporting
confidence: 91%
“…The data collected in both online and laboratory settings produced similar results. These findings are in line with studies showing no significant differences in results of online and in lab experiments (Buso, I.M., Di Cagno, D., Ferrari, L. et al 2021). Earlier studies have established that the perceptual nature of the experiment does not get significantly influenced by the experimental setting (Germine, L., Nakayama, K., Duchaine, B.C.…”
Section: Resultssupporting
confidence: 91%
“…At the same time, since our participants were not monitored by video camera, we cannot rule out the second problem. Nevertheless, previous studies 63 65 demonstrated that in online experiments without participant video monitoring, there was no significant difference in social preferences (e.g., fairness and cooperation) compared with laboratory experiments. One of those studies 65 compared the results of online protocols with and without participant video monitoring with the results of a laboratory protocol for three standard economic games: ultimatum, dictator, and public good, finding only minor differences in the choice data, which indirectly supports the internal validity of our results.…”
Section: Discussionmentioning
confidence: 86%
“…We performed our lab-in-the-field in August 2017, i.e., long before the COVID-19 pandemics, which has dramatically increased the frequency of online experiments, with researchers significantly improving techniques to recruit representative subject pools, implement video controls during the experiment, and perform payment procedures credible to subjects (see, e.g., Buso et al 2021 ). At the same time, by replicating traditional laboratory experiments, experimental economists have shown that lab-like findings from online experiments are not so far from those previously found in the laboratory (see, e.g., Buso et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%